Phosphorus-based polymers from synthesis to applications - Monge, Sophie; David, Ghislain (RSC polymer chemistry series ;, 2014)
Phosphorus-containing (co)polymers are gaining wide appeal for many uses, from healthcare and medicine to energy and environmental applications. Phosphorus-Based Polymers is the first book dedicated to this topic and provides a comprehensive overview of the different polymers and their uses. The first part of the book covers the synthesis and polymerisation of different phosphorus containing systems including phosphorus containing (meth)acrylate, (meth)acrylamide and viny or allyl monomers, as well as vinyl phosphonic acid, 2-methacryloyloxyethyl phosphorylcholine, poly(phosphoesters)and polyphosphazenes. The second part of the book contains specific chapters detailing different applications such as biomedical applications in dental materials, tissue engineering and drug delivery, metal complexation for anti-corrosion and wastewater purification materials, fire retardant additives and fuel cell membranes. Written by expert researchers in the chemistry of phosphorus-containing polymers, this book is suitable for academic and industrial researchers interested in polymer and materials synthesis as well as their applications.